The Role of Occupational Therapy in Secondary Prevention of Diabetes - Xizi Shen; Xingping Shen (International Journal of Endocrinology, 2019)
Diabetes mellitus is becoming a global health concern due to its prevalence and projected growth. Despite a growing number of interventions for secondary prevention of diabetes, there is a persistent poor glycemic control and poor adherence to the prescribed diabetes management regimen. In light of the tremendous costs of diabetes to both individuals and the society, it is pressing to find effective ways to improve diabetes self-management (DSM) and treatment adherence. Occupational therapists can bring values to the diabetes care team by evaluating multiple levels of influence on DSM, addressing personal and environmental barriers to well-being and DSM, and supporting patients to develop of a highly complex competences and skills to satisfactorily self-manage diabetes. This article summarizes two evidence-based, well-structured occupational therapy (OT) programs that use activity-based treatments and psychosocial strategies, respectively, to improve DSM abilities and to enhance quality of life. As the needs of adolescents with diabetes are quite different from other diabetic populations, this article also provides a summary of pediatric OT interventions that aim to facilitate autonomy and development of DSM ability among adolescents with diabetes. Evidence indicates that OT interventions can improve the quality of life and treatment adherence in patients with diabetes and hence should be continued and built on to address the increasing needs of diabetic populations.